The young entrepreneurs of Europe and the role of international mobility - Monica Roman; Dorel Mihai Paraschiv (Amfiteatru Economic Journal, 2019)
The Single European Market and the warranty of freedom of movement of goods and people within the European Union has made an impact in the share of European youth travelling internationally. This phenomenon has brought countless advantages including increased economic performance on the labor market, development of entrepreneurial actions and even personal growth. This paper estimates the impact of international mobility in Europe on youth entrepreneurship, after the individual's returning in the country of origin. The data source for this study is a European survey launched within the Horizon 2020 project MOVE "Mapping mobility - pathways, institutions and structural effects of youth mobility in Europe". Using Prosperity Score Matching on a generous sample providing data on both mobile and non-mobile respondents, we prove that people have double chances of becoming entrepreneurs if they had an intra-European mobility experience. Even though mobility has been shown to have statistically significant benefits, it only affected the entrepreneurship of European youth in a conservative way explained by the factors that encourage the youth to travel abroad.
Keywords: J13; J61; L26; 330; Youth intra-European Mobility; Young Entrepreneurs; Propensity Score Matching; Europe